Enamel matrix proteins associated with GTR and bioactive glass in the treatment of class III furcation in dogs Proteína da matriz do esmalte associada a R.T.G. e vidro bioativo no tratamento de furca grau III em cães - José Marcos Alves Fernandes; Rodrigo Otávio Citó César Rego; Luis Carlos Spolidorio; Rosemary Adriana Chiérici Marcantonio; Elcio Marcantonio Júnior; Joni Augusto Cirelli (Sociedade Brasileira de Pesquisa Odontológica, 2005)
This study investigated, both histologically and histometrically, the efficacy of enamel matrix derived proteins (EMD) associated with bioactive glass (BG) and an absorbable membrane in the treatment of class III furcation defects in mongrel dogs. After surgical defect creation and chronification, the lesions were randomly divided into three groups according to the treatment employed: Test Group 1 - EMD + BG + membrane, Test Group 2 - EMD + membrane and Control Group - BG + membrane. After a 90-day healing period, the dogs were sacrificed. The descriptive analysis and the histometric data showed similar results for the experimental groups in all studied parameters (MANOVA, p > 0.05). The association of Emdogain® with bioglass and GTR, or with GTR only, showed similar results when compared with the ones obtained with bioglass associated with membrane in the treatment of class III furcation defects in dogs. The three modalities of treatment showed partial filling of the furcations, with bone and cementum regeneration limited to the apical portion of the defects. Este estudo investigou, histológica e histometricamente, a eficácia da proteína derivada da matriz de esmalte (EMD) associada com vidro bioativo (BG) e membrana absorvível, no tratamento de defeitos de furcas classe III em cães. Após criação cirúrgica e cronificação dos defeitos, as lesões foram divididas aleatoriamente em três grupos de acordo com o tratamento proposto: Grupo Teste 1 - EMD + BG + membrana, Grupo Teste 2 - EMD + membrana e Grupo Controle - BG + membrana. Após 90 dias do período de cicatrização, os cães foram sacrificados. A análise descritiva e os dados histométricos mostraram resultados similares para os grupos experimentais em todos os parâmetros estudados (MANOVA, p > 0,05). As associações de Emdogain com vidro bioativo e RTG, ou somente com RTG, mostraram resultados similares quando comparadas ao vidro bioativo associado à membrana no tratamento de defeito de furca classe III, em cães. As três modalidades de tratamento mostraram preenchimento parcial das furcas com regeneração óssea e cementária limitada à porção apical das mesmas.